The major's daughter - Jennings, Regina (Regina Lea) (Jennings, Regina (Regina Lea). Fort Reno series., 2019)
"Caroline Adams returns to Indian Territory craving adventure after living society life. When she comes across outlaw Frisco Smith, his dreams to obtain a piece of property on the Unassigned Lands are persuasive. When the gun sounds, they find themselves battling over a claim-and both dig in their heels"--